Governmentality Within Collaborative Tourism Governance of The Nature Based Tourism - Sentanu, I Gede Eko Putra Sri; Putra, Fadillah; Sakti, Trenggono Pujo; Fauzen, Ahmad; Kumalasari, Klara (JESS (Journal of Education on Social Science); Vol 8 No 02 (2024): Agustus 2024, 2024)
The tourism sector is a potential that must continue to be developed. Tourism is part of a strategic industrial sector and can generate foreign exchange. The development of the tourism sector shows a shift in the tourist travel model from industry tourism towards sustainability tourism which focuses more on nature-based tourism activities. Management of nature-based tourism is critical for society and the environment with basic resources. Apart from that, managing nature-based tourism in Bali is requires support from the government and other actors to enchance tourist attraction and encourage regional development. The research purpose to analyze the governance of tourism collaboration in managing nature-based tourism. This research of critical theory on collaborative tourism governance through participation (sovereignty, disciplinary, and neo-liberal) as knowledge rules that governing tourism behavior. A critical perspective on collaborative governance within this framework would examine how ostensibly participatory and collaborative forms of governance in fact operate as techniques of power and control. The collaborative governance arrangements may be used by authorities to extend their reach and influence, by incorporating tourist citizens and civil society into governmental processes in governance nature-based tourism. This research uses the data collection literature study research method, namely by collecting, examining information or data about the results of different findings but still within the same theme from books, proposals, various applicable articles and journals, then compiling, explaining, so as to obtain conclusions. This research will show how governmentality of the operates both in tourism destinations and on a wider scale, often misses the link in conditioning tourist behavior and makes governance inefficient.